Energy Prospective Model For The Forecast of Future Scenarios in Colombia: Escenarios de sectores de consumo de energía - Hernández Bueno, Nelson Javier (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This investigation presents the development of a prospective model for the forecast of energy consumption scenarios of the consumption sectors in Colombia, based on the economic factor of the country. The study implements a multiple regression analysis, together with multi-criteria decision making to establish an integrated methodology and forecast the behavior of future scenarios of energy demand by the final consumption sectors. The transport, commercial, industrial, residential, agriculture, mining and construction sectors were taken as a study.